2021
DOI: 10.1186/s12876-021-01761-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma interleukin-17 and alpha-fetoprotein combination effectively predicts imminent hepatocellular carcinoma occurrence in liver cirrhotic patients

Abstract: Background Predicting imminent hepatocellular carcinoma (HCC) in liver cirrhotic patients is an unmet medical need. We aimed to investigate circulatory biomarkers and their optimum combinations in a prospective study. Methods We investigated plasma interleukin 17 (IL-17) concentrations, quantified using enzyme-linked immunosorbent assay (ELISA), for the prediction of HCC in a large cohort of 404 HCC-naïve liver cirrhotic patients regularly followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…The results of current study showed that there were significant correlations between the level of IgE and transaminases (ALT, AST) and between IgE and AFP in both study groups (group I and group II), which agreed with some previous studies 23,34 . However, these were in contradictory to findings of other studies 25,33 , who reported negative association between IgE and transaminases.…”
Section: Discussionsupporting
confidence: 93%
“…The results of current study showed that there were significant correlations between the level of IgE and transaminases (ALT, AST) and between IgE and AFP in both study groups (group I and group II), which agreed with some previous studies 23,34 . However, these were in contradictory to findings of other studies 25,33 , who reported negative association between IgE and transaminases.…”
Section: Discussionsupporting
confidence: 93%
“…Circulating blood IL-17 concentration is also considered to be a predictive factor of hepatocellular carcinoma (HCC) in patients with liver cirrhosis. The combination of alpha-fetoprotein (AFP) and IL-17 has a high sensitivity for predicting HCC within 1 year (13). In the NASH-HCC model, the inflammatory factor FGF21 can inhibit liver cells-TLR4-IL-17-A signaling pathway to prevent the conversion of NASH to HCC (14).…”
Section: Introductionmentioning
confidence: 99%
“…Gene signature risk models were derived using the generalized iterative modeling approach, a type of machine learning approach which performs empirical maximization with respect to either the log likelihood in the proportional hazards model [ 30 ] or the area under the receiver operating characteristic curve in classification analysis [ 31 ]. In this study, we selected to maximize the log likelihood in the time-to-MIBC survival analysis.…”
Section: Methodsmentioning
confidence: 99%